Pengaruh Variety Seeking dan Packaging terhadap Brand Switching Studi Konsumen Natasha Skincare di Bandar Lampung - Dwi Apriliani; A Zuliansyah; Vicky F Sanjaya (Universitas Bumigora, 2021)
This study uses a quantitative approach. The research was conducted on Natasha skincare consumers in Bandar Lampung. The research sample amounted to 100 respondents using non-probability sampling technique, namely purposive sampling. Collecting data through the distribution of questionnaires. The data analysis method in this study uses partial least squares structural equation modeling (PLS-SEM) with SmartPLS3 software for data processing. The results show that the hypothesis is supported, namely that there is a positive and significant effect between variety seeking (X1) on brand switching (Y) on Natasha skincare consumers in Bandar Lampung. This is evidenced by the original sample (O) 0.438 T-statistic value 4.553 > 1.96 and P-Values ​​0.000 < 0.05, and there is a positive and significant effect between packaging (X2) on brand switching (Y) with an original sample value (O) of 0.343, a T-Statistic value of 3.197 > 1.96 and a P-Values ​​of 0.001 < 0.05. Based on R2, which is 0.464 or 46.4%, which means that variety seeking and packaging are able to explain the variability of the brand switching construct by 46.4%, and the remaining 54.6% is influenced by other factors not examined in this study. variety seeking and packaging for brand switching on Natasha skincare consumers in Bandar Lampung.